Analysis of energy cascade utilization in a chemically recuperated scramjet with indirect combustion. (1st November 2016) - Qin, Jiang; Cheng, Kunlin; Zhang, Silong; Zhang, Duo; Bao, Wen; Han, Jiecai
Abstract: The working process of scramjet with regenerative cooling, which was actually the chemical recuperation process, was analyzed in view of energy cascade utilization. The indirect combustion was realized through pyrolysis reaction of fuel. The relative yields of thermal exergy obtained by indirect combustion have been predicted both assuming an ideal pyrolysis reaction and using the experimental results of thermal pyrolysis of n-decane. The results showed that the influence mechanism of regenerative cooling improved the scramjet engine performance by the energy cascade utilization, and the combustion process was supposed to be designed with the cooling process together to utilize the chemical energy of fuel in a more effective way. A maximum value of 11% of the relative yield was obtained with the ideal pyrolysis reaction while a value less than 3% existed in the thermal pyrolysis experiments because of the domination of chemical kinetics rather than chemical thermodynamics in the real experiments. In spite of the difference between the ideal and the present experimental results, the indirect combustion was prospective to achieve a better energy cascade utilization in a chemically recuperated scramjet if the pyrolysis reaction was further optimized. The results in this paper were beneficial for the performance optimization of a regenerative cooling scramjet. Highlights: A new method of energy cascade utilization in a chemically recuperated scramjet. 11% exergy loss is reduced by ideal pyrolysis reaction with indirect combustion. Regenerative cooling with chemical recuperation can improve engine performance.